2020
DOI: 10.1002/pssb.202000052
|View full text |Cite
|
Sign up to set email alerts
|

Polyamorphism of GeO2 Glass at High Pressure

Abstract: Polyamorphism of network‐forming SiO2 and GeO2 glasses at high pressures is a puzzling topic in condensed matter physics and has long‐standing interest because of their important geophysical and geochemical implications. Molecular dynamics simulations suggest that there are multiple amorphous–amorphous transitions at high pressure with parallel high‐pressure crystalline counterparts. However, it is very challenging to experimentally distinguish the pressure‐induced subtle change in the amorphous state at high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
0
5
1
Order By: Relevance
“…Such similarities indicate that the CN O of GeO 2 glass above 55 to 148 GPa is expected to be similar to that of the pyrite-type phase. Although there is no experimental result for compressed GeO 2 glass beyond 101 GPa, earlier elastic X-ray studies up to ∼90 GPa also suggested the formation of pyrite-like amorphous structures. ,,, As our IXS results distinguish the PDOS features for [3] O and [3+1] O topologies, and the current IXS results of GeO 2 glass show characteristic pattern for [3+1] O topology toward and beyond Mbar, the oxygen environments in amorphous structures may not be fully described with [3] O only. Although there is no experimental study on oxygen configurations in GeO 2 glass at high pressures, particularly above 100 GPa, information regarding CN O can be obtained from CN Ge ; pressure-induced decrease in the O–Ge–O angle in the glass above 50 GPa from simulations indicates an increase in average CN Ge > 6, consistent with experimental results .…”
Section: Resultscontrasting
confidence: 76%
See 2 more Smart Citations
“…Such similarities indicate that the CN O of GeO 2 glass above 55 to 148 GPa is expected to be similar to that of the pyrite-type phase. Although there is no experimental result for compressed GeO 2 glass beyond 101 GPa, earlier elastic X-ray studies up to ∼90 GPa also suggested the formation of pyrite-like amorphous structures. ,,, As our IXS results distinguish the PDOS features for [3] O and [3+1] O topologies, and the current IXS results of GeO 2 glass show characteristic pattern for [3+1] O topology toward and beyond Mbar, the oxygen environments in amorphous structures may not be fully described with [3] O only. Although there is no experimental study on oxygen configurations in GeO 2 glass at high pressures, particularly above 100 GPa, information regarding CN O can be obtained from CN Ge ; pressure-induced decrease in the O–Ge–O angle in the glass above 50 GPa from simulations indicates an increase in average CN Ge > 6, consistent with experimental results .…”
Section: Resultscontrasting
confidence: 76%
“…16 X-ray absorption spectroscopy (XAS) and molecular dynamics (MD) studies have reported a gradual transformation of [6] Ge to [7] Ge up to 100 GPa. 20,26,30,31 In contrast, a recent X-ray-emission study indicated that CN Ge remains at 6 up to ∼101 GPa. 32 Such a discrepancy may be due in part to the structural complexity of amorphous oxides under extreme compression.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The pressure-induced local structural changes of GeO 2 glass have been extensively studied using x-ray-absorption spectroscopy [7][8][9][10], x-ray diffraction (XRD) [11][12][13][14][15][16], neutron diffraction (ND) [17][18][19][20][21], inelastic x-ray scattering [22,23], x-ray Raman scattering at the oxygen K-edge [24,25], x-ray emission spectroscopy [26], and a number of theoretical studies such as classical [27][28][29] and first-principles molecular dynamics simulations [30][31][32]. Important structural and spectroscopic details on the local short-range order (SRO) and the intermediate-range order (IRO) of GeO 2 glass under compression have been successfully revealed [3,6,18,33]. Mainly based on the SRO, pressure-induced multiple polyamorphs in GeO 2 glass have been recognized, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Studies which targeted the exploring the polymorphic phases of GeO 2 -SiO 2 glasses indicated the existence of three polymorphic phases, named, α-quartz-like, rutile-like, and pyrite-like amorphous structures. [11] The occurrences of these pressure-induced polymorphic structures in the GeO 2 -SiO 2 system are still ambiguous and of unknown reasons. However, it is mentioned that the accumulation of positively charged ions around oxygen atoms in SiO 2 is more pronounced than the accumulation around oxygen atoms in GeO 2 [12] for cations having the same ionic radius.…”
mentioning
confidence: 99%